Endothelial SHIP2 plays a critical role in glucose regulation and insulin sensitivity. (22nd September 2015) - Gage, M; Wheatcroft, S; Abbas, A; Cubbon, R; Surr, J; Schurmans, S; Jacoby, M; Dubois, E; Kearney, M
Abstract : Introduction: Insulin resistance, which underpins type 2 diabetes, obesity and metabolic syndrome, is an independent risk factor for cardiovascular disease and promotes atherosclerosis through its association with endothelial dysfunction. We recently demonstrated that insulin resistance specific to endothelium decreases nitric oxide bioavailability and increases reactive oxygen species. Accumulating evidence suggests that the relationship between insulin resistance and endothelial function is reciprocal; however, the role of the endothelium in whole-body glucose regulation remains controversial. The lipid phosphatase SHIP2 acts as a negative regulator of insulin signalling. In this study we generated endothelial-specific SHIP2 haploinsuffient mice using Cre-LoxP technology to determine whether enhanced insulin signalling in endothelium favourably modulates vascular function and whole-body glucose regulation. Methods: To establish endothelial cell SHIP2 knockout mice, we crossed transgenic mice expressing Cre recombinase under the control of Tie2 promoter/enhancer (Tie2-Cre Tg; Jackson Laboratory) with mice harbouring SHIP2 alleles flanked by loxP sites (SHIP2floxed). Male EC-SHIP2+/− offspring were compared with control littermates at 12–15 weeks of age. The metabolic phenotype was assessed in response to intraperitoneal glucose (1 mg/g) and insulin (50 U/kg) tolerance tests. Blood pressure was measured by tail cuff plethysmography. Vascular function was quantified ex vivo in the thoracic aorta by constructing concentration–response curves for constriction to phenylephrine and relaxation to acetylcholine and sodium nitroprusside (SNP) (all 1 nmol to 10 mmol). Results: EC-SHIP+/− mice exhibited normal development. Body mass and organ masses were similar in both groups of mice, with the exception of heart mass, which was greater in EC-SHIP+/− mice (table 1). No significant differences were observed in heart rate or blood pressure (table 1). Glucose tolerance after intraperitoneal glucose challenge was significantly better in EC-SHIP+/− than controls (fig 1; p⩽0.05). There were no differences in plasma insulin concentrations, either fasted or after glucose challenge (table 2), suggesting that the improved glycaemia in EC-SHIP+/− mice was caused by enhanced insulin sensitivity. Improved insulin sensitivity was confirmed in EC-SHIP+/− mice in insulin tolerance tests (fig 2) (p⩽0.05). Preliminary data from ex-vivo studies in aorta revealed no significant differences between EC-SHIP+/− and controls in constriction to phenylephrine or in maximal relaxation to acetylcholine or SNP. Conclusion: Endothelial partial deletion of SHIP2 improves glucose tolerance and insulin sensitivity in mice. These data support a critical role for endothelial cells in whole-body glucose regulation and suggest that endothelial insulin signalling is an appropriate target to improve insulin sensitivity. Effects of endothelial SHIP2 modulation on vascular function require further investigation.